Method for producing a precursor of a positive electrode active material and method for producing a positive electrode active material
Patent Information
- Application Number
- JP2025064483
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-22
Smart Images

Figure 2026170728000001_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a method for producing a precursor of a cathode active material. This disclosure also relates to a method for producing a cathode active material. [Background technology]
[0002] Lithium-ion secondary batteries are widely used in various fields, such as power sources for vehicle propulsion and portable power supplies. In the production of positive electrode active materials used in the positive electrode of lithium-ion secondary batteries, typically, hydroxides or carbonates containing a metal source other than Li are first produced as precursors by crystallization. For example, when producing carbonates, which are precursors to lithium transition metal composite oxides, a crystallization reaction is carried out using a reaction solution containing transition metals, ammonium ions, and carbonate ions (see, for example, Patent Document 1).
[0003] On the other hand, in recent years, material recycling of used lithium-ion secondary batteries has been promoted from the perspective of SDGs. Regarding material recycling, technologies are being developed to separate the metal elements contained in the positive electrode active material from used lithium-ion secondary batteries and reuse them in the manufacture of positive electrode active material. For example, ammonia leaching can be used to obtain an ammonia leachate containing Ni and Co from battery waste (see, for example, Non-Patent Document 1). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] International Publication No. 2017 / 119457 [Non-patent literature]
[0005] [Non-Patent Document 1] Waste Management, February 2017, vol.60, p.680-688 [Overview of the project] [Problems that the invention aims to solve]
[0006] As a result of diligent research by the present inventors, the following has been discovered: In the material recycling of lithium-ion secondary batteries, ammonia leaching can be used to obtain a leachate containing Ni, Co, Mn, ammonia, ammonium ions, and carbonate ions. Furthermore, by evaporating the ammonia from this leachate, nickel-cobalt-manganese composite carbonate, a precursor of the positive electrode active material, can be produced. However, in this case, Mn precipitates preferentially first, and in the carbonate particles finally obtained, there is a problem that Mn is unevenly distributed in the center of the particles. When Mn is unevenly distributed in the center of the particles, the amount of Ni in the surface layer increases, which can lead to instability of the crystal structure of the positive electrode active material.
[0007] Therefore, the present disclosure aims to provide a method for producing a cathode active material precursor in which the uneven distribution of Mn in the particle center is suppressed. [Means for solving the problem]
[0008] The present disclosure provides a method for producing a precursor of a positive electrode active material, comprising the step of adding a raw material solution containing Ni, Co, Mn, ammonia, ammonium ions, and carbonate ions to a precipitation solution to precipitate a carbonate containing Ni, Co, and Mn. The concentration of ammonia in the precipitation solution is lower than the concentration of ammonia in the raw material solution.
[0009] This configuration makes it possible to produce a precursor of a positive electrode active material in which the uneven distribution of Mn in the particle center is suppressed. [Brief explanation of the drawing]
[0010] [Figure 1] Figure 1 is a flowchart showing the steps involved in the recycling of lithium-ion secondary battery waste, including the steps for the method of producing the cathode active material precursor of this disclosure. [Figure 2] Figure 2 is a schematic longitudinal cross-sectional view showing the internal structure of an example of a lithium-ion secondary battery. [Figure 3] FIG. 3 is a schematic exploded view showing the configuration of the electrode assembly of the lithium ion secondary battery shown in FIG. 2. [Figure 4] FIG. 4 is a cross-sectional SEM image of the nickel-cobalt-manganese composite carbonate particles obtained in Comparative Example 1. [Figure 5] FIG. 5 is a cross-sectional Mn mapping image of the nickel-cobalt-manganese composite carbonate particles obtained in Comparative Example 1. [Figure 6] FIG. 6 is a cross-sectional Ni mapping image of the nickel-cobalt-manganese composite carbonate particles obtained in Comparative Example 1. [Figure 7] FIG. 7 is a cross-sectional SEM image of the nickel-cobalt-manganese composite carbonate particles obtained in Example 4. [Figure 8] FIG. 8 is a cross-sectional Mn mapping image of the nickel-cobalt-manganese composite carbonate particles obtained in Example 4. [Figure 9] FIG. 9 is a cross-sectional Ni mapping image of the nickel-cobalt-manganese composite carbonate particles obtained in Example 4. [Modes for Carrying Out the Invention]
[0011] Hereinafter, embodiments according to the present disclosure will be described with reference to the drawings. Matters that are not mentioned in the present specification and are necessary for implementing the present disclosure can be grasped as design matters of those skilled in the art based on the conventional technology in the relevant field. The present disclosure can be implemented based on the contents disclosed in the present specification and the common general technical knowledge in the relevant field. In the following drawings, members and portions having the same function are denoted by the same reference numerals in the description. The dimensional relationships (length, width, thickness, etc.) in each drawing do not reflect the actual dimensional relationships. It should be noted that the numerical range expressed as "A to B" in the present specification includes A and B.
[0012] In this specification, "secondary battery" refers to an energy storage device that can be repeatedly charged and discharged. Furthermore, in this specification, "lithium-ion secondary battery" refers to a secondary battery that uses lithium ions as a charge carrier and achieves charging and discharging through the transfer of charge associated with lithium ions between the positive and negative electrodes.
[0013] This disclosure relates to a method for producing the precursor of the positive electrode active material of this disclosure, which involves nickel (Ni), cobalt (Co), manganese (Mn), ammonia (NH3), and ammonium ions (NH4). + ), and carbonate ions (CO3 2- The process includes adding a raw material solution containing ) to a precipitation solution to precipitate carbonates containing Ni, Co, and Mn (hereinafter also referred to as the "crystallization process"). Here, the concentration of ammonia in the precipitation solution is lower than the concentration of ammonia in the raw material solution.
[0014] The raw material liquid used in the manufacturing method of this disclosure can be generated during the recycling of lithium-ion secondary battery waste. Therefore, Figure 1 shows the steps of a series of recycling processes for lithium-ion secondary battery waste utilizing the manufacturing method of the cathode active material precursor of this disclosure. Note that in Figure 1, the crystallization step S101 is an essential step in the manufacturing method of the cathode active material precursor of this disclosure, and the other steps are optional.
[0015] Therefore, the method for producing the precursor of the positive electrode active material described herein may relate to the material recycling of secondary batteries (particularly lithium-ion secondary batteries). First, a general example of the configuration of a lithium-ion secondary battery will be described.
[0016] <Lithium-ion rechargeable battery> Examples of lithium-ion secondary battery structures are shown in Figures 2 and 3. Figure 2 is a schematic longitudinal cross-sectional view showing the internal structure of an example lithium-ion secondary battery. Figure 3 is a schematic exploded view showing the electrode body of the lithium-ion secondary battery shown in Figure 2. The following description of lithium-ion secondary batteries is for the purpose of understanding and does not in any way limit the method of manufacturing the precursor of the positive electrode active material of this disclosure.
[0017] As shown in Figure 2, the lithium-ion secondary battery 100 is a sealed battery in which a flat-shaped electrode body 20 and a non-aqueous electrolyte (not shown) are housed inside a battery case 30. As shown in Figure 2, the battery case 30 consists of an outer casing 32 that houses the electrode body 20 and a lid 34 that seals the opening of the outer casing 32. The outer casing 32 and the lid 34 are sealed by welding, such as by laser welding. For example, aluminum, aluminum alloy, or resin can be used as the material for the battery case 30.
[0018] In the illustrated example, the battery case 30 is rectangular. However, the shape of the battery case 30 is not limited to this, and it may be cylindrical, for example. Alternatively, the battery case 30 may be a laminated case having a gas barrier layer, such as an aluminum layer, and a sealant layer containing a thermoplastic resin.
[0019] The battery case 30 is equipped with a positive electrode terminal 42 and a negative electrode terminal 44 for external connection. The battery case 30 is also provided with a safety valve 36 that is set to release the internal pressure if the internal pressure of the battery case 30 rises above a predetermined level. The battery case 30 is provided with an inlet (not shown) for injecting a non-aqueous electrolyte. The positive electrode terminal 42 is electrically connected to the positive electrode current collector plate 42a. The negative electrode terminal 44 is electrically connected to the negative electrode current collector plate 44a.
[0020] As shown in Figures 2 and 3, the electrode body 20 has a configuration in which a long positive electrode sheet 50 and a long negative electrode sheet 60 are superimposed on each other via two long separator sheets 70 and wound in the longitudinal direction. Therefore, in this embodiment, the electrode body 20 is a wound electrode body. However, the electrode body 20 is not limited to this, and may be a laminated electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked via separators.
[0021] As shown in Figure 2, in the positive electrode sheet 50, a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (in this case, both sides) of the positive electrode current collector 52. The positive electrode sheet 50 has a portion 52a where the positive electrode active material layer 54 is not formed and the positive electrode current collector 52 is exposed. A positive electrode current collector plate 42a is bonded to the portion 52a where the positive electrode active material layer is not formed.
[0022] Examples of positive electrode current collectors 52 constituting the positive electrode sheet 50 include aluminum foil. The positive electrode active material layer 54 contains a positive electrode active material. The positive electrode active material is typically a lithium nickel cobalt manganese composite oxide. The positive electrode active material layer 54 may also contain conductive materials (e.g., carbon black, carbon nanotubes, etc.), binders (e.g., polyvinylidene fluoride, etc.), etc.
[0023] The content of positive electrode active material in the positive electrode active material layer 54 is preferably 70% by mass or more, and more preferably 85% by mass or more and 99% by mass or less. The content of conductive material in the positive electrode active material layer 54 is preferably 0.1% by mass or more and 20% by mass or less, and more preferably 0.3% by mass or more and 15% by mass or less. The content of binder in the positive electrode active material layer 54 is preferably 0.4% by mass or more and 15% by mass or less, and more preferably 0.5% by mass or more and 10% by mass or less.
[0024] As shown in Figure 3, in the negative electrode sheet 60, a negative electrode active material layer 64 is formed along the longitudinal direction on one or both sides (in this case, both sides) of the negative electrode current collector 62. The negative electrode sheet 60 has a portion 62a where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed. A negative electrode current collector plate 44a is bonded to the portion 62a where the negative electrode active material layer is not formed.
[0025] An example of a negative electrode current collector 62 constituting the negative electrode sheet 60 is copper foil. The negative electrode active material layer 64 contains a negative electrode active material. Examples of negative electrode active materials include carbon-based negative electrode active materials (e.g., graphite, hard carbon, soft carbon, etc.). The negative electrode active material layer 64 may also contain a binder (e.g., styrene-butadiene rubber (SBR), etc.) and a thickener (e.g., carboxymethylcellulose (CMC), etc.).
[0026] The graphite content in the negative electrode active material layer 64 is preferably 90% by mass or more, and more preferably 95% by mass or more and 99% by mass or less. The binder content in the negative electrode active material layer 64 is preferably 0.1% by mass or more and 8% by mass or less, and more preferably 0.5% by mass or more and 3% by mass or less. The thickener content in the negative electrode active material layer 64 is preferably 0.3% by mass or more and 3% by mass or less, and more preferably 0.5% by mass or more and 2% by mass or less.
[0027] Examples of separators 70 include porous resin sheets such as polyethylene and polypropylene. The porous sheet may have a single-layer structure or a multi-layer structure. A heat-resistant layer (HRL) may be provided on the surface of the separator 70.
[0028] Non-aqueous electrolytes typically contain a non-aqueous solvent and a supporting salt (in other words, an electrolyte salt). Examples of non-aqueous solvents include carbonates (e.g., EC, ethyl methyl carbonate, dimethyl carbonate, etc.), esters, ethers, etc. Examples of supporting salts include lithium salts such as LiPF6. The concentration of the supporting salt is not particularly limited, but is preferably 0.7 mol / L to 1.3 mol / L. Non-aqueous electrolytes may also contain various additives such as gas generating agents and film-forming agents. In this embodiment, a non-aqueous electrolyte is used as the electrolyte, but the electrolyte may be a solid electrolyte.
[0029] The lithium-ion secondary battery 100 is used, for example, in automotive applications (i.e., as a power source for vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs)), and as a power source for electronic devices.
[0030] As described above, in lithium-ion secondary batteries, Li, Ni, Co, and Mn are typically used as constituent metal elements of the lithium nickel cobalt manganese composite oxide, which is the positive electrode active material. Al is commonly used as the positive electrode current collector. Cu is commonly used as the negative electrode current collector. In addition, Li is used as the non-aqueous electrolyte in lithium-ion secondary batteries. Al may also be used for the battery case.
[0031] <Each stage of recycling lithium-ion secondary battery waste> The recycling of lithium-ion secondary battery waste will be explained with reference to Figure 1. Lithium-ion secondary battery waste includes, for example, used lithium-ion secondary batteries and defective lithium-ion secondary batteries. Typically, this waste contains, as major elements, Li, Ni, Co, Mn, and O derived from the positive electrode active material; Al derived from the positive electrode current collector; C derived from the negative electrode active material; Cu derived from the negative electrode current collector; Li derived from the non-aqueous electrolyte; and Al derived from the battery case. Note that lithium-ion secondary battery waste may also consist of waste components such as electrodes. The metallic elements shown in Figure 1 may take the form of oxides, carbonates, etc., as will be described later.
[0032] As shown in Figure 1, the recycling (i.e., the recycling method) includes a crushing step S10 to crush lithium-ion secondary battery waste, a sorting step S20 to sort the crushed material obtained in the crushing step S10 and remove metal fragments, a roasting step S30 to reduce and roast the black mass obtained in the sorting step S20, a first ammonia leaching step S40 to remove Cu from the roasted black mass by leaching ammonia from the roasted black mass obtained in the roasting step S30, and a first ammonia leaching step S40 to remove Ni 2+ Co 2+ Mn 2+ NH3, NH4 + CO3 2-The recycling process includes a second ammonia leaching step S50 to obtain a leachate containing the above. In addition, the recycling process includes a crystallization step S101 in which the leachate is used as a raw material, and the raw material is added to a precipitation solution to precipitate carbonates containing Ni, Co, and Mn.
[0033] <Crushing process S10> In this recycling process, a crushing step S10 is performed to crush the lithium-ion secondary battery waste. The crushing step 10 can be carried out according to a known method. For example, the lithium-ion secondary battery waste can be crushed using a known crushing device such as a crusher, pulverizer, or de-crusher. This yields crushed lithium-ion secondary battery waste.
[0034] In the crushing step S10, it is not necessary to crush the entire lithium-ion secondary battery waste. For example, the battery case of the lithium-ion secondary battery may be opened, the electrode body may be removed, and only the electrode body may be crushed. In this case, the constituent materials of the battery case can be removed efficiently.
[0035] Furthermore, pretreatment of the lithium-ion secondary battery waste may be performed before the crushing step S10. For example, a discharge treatment step may be performed before the crushing step S10 to discharge the lithium-ion secondary battery waste. This makes the recycling of lithium-ion secondary battery waste safer. The discharge treatment can be performed according to a known method.
[0036] <Sorting process S20> Next, in this recycling process, a sorting step S20 is performed to separate the above-mentioned crushed material and remove the metal fragments. Typical examples of metal fragments are fragments of the battery case, fragments of the positive electrode current collector, and fragments of the negative electrode current collector. Typically, the battery case fragments contain Al, the positive electrode current collector fragments contain Al, and the negative electrode current collector fragments contain Cu.
[0037] The sorting process S20 can be carried out according to known methods. Specifically, for example, the crushed material can be sieved to remove metal fragments. Alternatively, magnetic separation may be performed depending on the material of the metal fragments.
[0038] By performing the sorting process S20, it is possible to remove most of the Al and Cu contained in the waste. Therefore, it is preferable to remove at least Al and Cu contained in the waste during the sorting process S20.
[0039] After the metal fragments are removed, a black powder is typically obtained. This black powder is called black mass. Therefore, black mass is obtained by performing the sorting process S20. The metal elements contained in black mass are typically Li, Ni, Co, Mn, Al, Cu, etc. Ni, Co, and Mn typically originate from the positive electrode active material and exist in the form of composite oxides. Al and Cu originate from metal fragments that could not be completely removed in the sorting process S20. In addition, black mass typically contains C, which originates from the negative electrode active material, etc.
[0040] <Roasting process S30> Next, in this recycling process, a roasting process S30 is performed in which the black mass is reductively roasted. Here, reductive roasting refers to roasting in which at least some of the metal in the metal oxides contained in the black mass is reduced. In particular, the roasting process reduces Ni and Co, which are in the form of complex oxides contained in the black mass, to their metallic components.
[0041] Such roasting is typically carried out in an atmosphere with an oxygen concentration of 5% by volume or less. Preferably, the oxygen concentration in this atmosphere is 1% by volume or less. Particularly preferred is an inert gas atmosphere such as argon or nitrogen.
[0042] The roasting temperature is, for example, 650°C to 1500°C, preferably 750°C to 1000°C. The roasting time can be appropriately selected according to the roasting temperature, for example, 1 hour to 24 hours, preferably 4 hours to 12 hours.
[0043] By carrying out the roasting process S30, roasted black mass can be obtained. Roasted black mass typically contains Li, Ni, Co, Mn, Al, Cu, and C. Li is typically in the form of Li2CO3. Mn is typically in the form of MnO. Ni, Co, Al, and Cu are typically in the form of metals.
[0044] Here, among the components contained in roasted black mass, Li2CO3 has particularly high solubility in water. Therefore, in this recycling process, a water leaching process may be carried out in which the roasted black mass is brought into contact with water to remove Li2CO3 from the roasted black mass.
[0045] When roasted black trout is brought into contact with water, the Li2CO3 contained in the roasted black trout preferentially dissolves in the water. Therefore, Li2CO3 can be preferentially moved to the aqueous phase and removed from the roasted black trout.
[0046] The water leaching process can be carried out according to known methods. Specifically, for example, it can be carried out by immersing roasted black mas in water and stirring as appropriate. Leaching may be carried out at room temperature or under heating.
[0047] <First ammonia leaching process S40> In this recycling process, a first ammonia leaching step S40 is performed, in which ammonia is leached from roasted black mass to remove Cu from the roasted black mass.
[0048] In the first ammonia leaching step S40, a first ammonia aqueous solution containing at least water and ammonia is used as the leaching agent for ammonia leaching of roasted black mass. The first ammonia aqueous solution may contain only water and ammonia, or it may contain other components. An example of other components is ammonium carbonate. If the first ammonia aqueous solution contains ammonium carbonate, the leaching rate of Cu can be increased.
[0049] As mentioned above, Li2CO3 has particularly high solubility in water, and also high solubility in the first ammonia aqueous solution. Therefore, if the water leaching process described above is not performed, or if Li2CO3 remains in the roasted black mass after the water leaching process, the first ammonia leaching process S40 can also remove Li2CO3 from the roasted black mass by ammonia leaching.
[0050] The concentration of ammonia in the first aqueous ammonia solution is not particularly limited as long as it can leach out Cu. From the viewpoint of suppressing the dissolution of metals other than Cu and Li, the concentration of ammonia in the first aqueous ammonia solution is preferably 0.01% by mass or more, and more preferably 0.1% by mass or more. Furthermore, the upper limit of the ammonia concentration is preferably 5% by mass or less, and more preferably 2% by mass or less. From the viewpoint of leaching ability and ease of handling, an ammonia concentration of 0.1% by mass to 2% by mass is particularly preferred.
[0051] The amount of ammonium carbonate in the first aqueous ammonia solution is preferably 0.5 to 1.5 molar times the amount of Cu contained in the roasted black mass, more preferably 0.8 to 1.2 molar times, and even more preferably equimolar. On the other hand, ammonium carbonate promotes the leaching of Ni and Co. The amount of ammonium carbonate in the first aqueous ammonia solution is preferably 0.20 molar times or less the total amount of Ni and Co contained in the roasted black mass, more preferably 0.10 molar times or less, and even more preferably 0.05 molar times or less.
[0052] The amount of the first ammonia solution used is not particularly limited and may be about the same as the amount of ammonia solution used in known ammonia leaching methods. For example, the amount of the first ammonia solution used is enough to completely immerse the roasted black mass.
[0053] Normally, oxygen is involved in the dissolution of Cu in aqueous ammonia. The first ammonia leaching step S40 may be carried out in the atmosphere using oxygen from the atmosphere. However, from the viewpoint of a high leaching rate, it is preferable to supply oxygen to the first aqueous ammonia solution during leaching. The amount of oxygen supplied is preferably in excess of the elements to be oxidized (i.e., Cu) contained in the roasted black mass.
[0054] Oxygen can preferably be supplied by introducing an oxygen-containing gas (e.g., oxygen gas, air, etc.) into the ammonia water by bubbling or the like. Oxygen can also be supplied by sealing a container and pressurizing it while introducing an oxygen-containing gas into it.
[0055] The first ammonia leaching step S40 can be carried out, for example, as follows: Prepare a container equipped with heating means such as a heater, temperature measuring means such as a thermometer or temperature sensor, stirring means such as a stirring blade or magnetic stirring bar, etc., as needed. Also, prepare a bubbling device as needed.
[0056] Roasted black muss and a primary ammonia aqueous solution are placed in a container. If necessary, oxygen-containing gas is supplied to the primary ammonia aqueous solution as bubbles using a bubbling device.
[0057] The leaching temperature is not particularly limited, but is preferably greater than 0°C and 80°C or less. More preferably it is between 10°C and 50°C, and even more preferably between 15°C and 35°C. The leaching time is not particularly limited, but is, for example, between 0.5 hours and 48 hours, preferably between 1 hour and 24 hours, and more preferably between 1.5 hours and 12 hours. Stirring is preferable during ammonia leaching. The stirring speed is not particularly limited, but is, for example, between 200 rpm and 2000 rpm, preferably between 300 rpm and 1000 rpm, and even more preferably between 400 rpm and 800 rpm.
[0058] Ammonia leaching can be terminated by performing solid-liquid separation such as filtration. Through ammonia leaching, Cu and Li selectively migrate to the aqueous phase. Therefore, as shown in Figure 1, this solid-liquid separation allows Cu 2+ -containing and Li + -containing aqueous phase (that is, Cu 2+ -containing and Li + -containing first aqueous ammonia solution) and a solid residue containing Ni, Co, Mn, Al and C to be obtained. As described above, the first ammonia leaching step S40 can be carried out.
[0059] Here, in the first ammonia leaching step S40, insoluble precipitates may form on the surface of the roasted black mass during ammonia leaching. These insoluble precipitates are considered to be compounds containing Ni, Co and Cu. These insoluble precipitates can be removed by performing ammonia leaching under a low oxygen concentration condition.
[0060] Therefore, as one embodiment of the first ammonia leaching step S40, the first ammonia leaching step S40 may be performed by leaching the roasted black mass using a first aqueous ammonia solution (A) with a concentration of 2.5 mol / L or less in the presence of oxygen, and then leaching the obtained solid residue using a first aqueous ammonia solution (B) under an inert gas atmosphere. According to this embodiment, the recovery rate of Cu is particularly high. As the leaching in the presence of oxygen, it is preferable to perform leaching while supplying a gas having an oxygen concentration of 21% by volume or more (for example, atmosphere, preferably oxygen gas) into the reaction vessel containing the first aqueous ammonia solution (A). As the method for supplying the gas, bubbling in which the gas is blown into the solution is preferred.
[0061] In this embodiment, it is preferable to supply oxygen gas into the reaction vessel containing the first aqueous ammonia solution (A). It is also preferable to supply an inert gas (e.g., nitrogen gas, etc.) into the reaction vessel containing the first aqueous ammonia solution (B). Bubbling, which involves blowing gas into the solution, is a preferred method of supply. The concentration of the first aqueous ammonia solution (A) is preferably 0.1 mol / L to 1.0 mol / L. The concentration of the first aqueous ammonia solution (B) is preferably 5 mol / L or higher, and more preferably 10 mol / L to 16.0 mol / L. This leaching with the first aqueous ammonia solution (A) and leaching with the first aqueous ammonia solution (B) may be repeated.
[0062] Furthermore, by evaporating the ammonia from the aqueous phase obtained in the first ammonia leaching step, Cu 2+ It can be precipitated and recovered as CuO. When a hydroxide (e.g., lithium hydroxide) is added to the aqueous phase and then the ammonia is evaporated, Cu 2+ It can be recovered as Cu(OH)2. When ammonia is evaporated, the lithium component remains dissolved in the aqueous phase, so Cu and Li can be separated by solid-liquid separation.
[0063] The evaporation of ammonia can be carried out according to known methods. For example, ammonia can be evaporated by placing the aqueous phase in an open container and heating it while stirring. The heating temperature is preferably 50°C or higher, more preferably 70°C or higher, and even more preferably 90°C or higher. The heating temperature may be below the boiling point of water (i.e., 100°C). The heating time is, for example, 0.5 hours or more and 24 hours or less, preferably 2 hours or more and 12 hours or less. The stirring speed is 200 rpm to 2000 rpm, preferably 400 rpm to 800 rpm.
[0064] The evaporated ammonia can be recovered using a known ammonia collection device. The recovered ammonia can be reused in processes that utilize ammonia in the recycling of lithium-ion secondary battery waste.
[0065] In addition, if chlorine gas is mixed into the roasting atmosphere during the roasting process S30, Li is obtained in the form of LiCl, and if hydrogen gas is mixed into the roasting atmosphere, Li is obtained in the form of LiOH. In this case as well, since these lithium compounds have high solubility in water, the first ammonia leaching process S40 can be carried out in the same manner.
[0066] <Second ammonia leaching process S50> In this recycling process, ammonia leaching is performed on the solid residue obtained in the first ammonia leaching step S40, and Ni 2+ Co 2+ Mn 2+ NH3, NH4 + CO3 2- A second ammonia leaching step S50 is performed to obtain a leachate containing [the specified substance].
[0067] In the second ammonia leaching step S50, the resulting leachate contains NH3 and NH4 + , and CO3 2- A decimal aqueous solution containing ammonia (NH3) and ammonium carbonate ((NH4)2CO3) is used as a leaching agent to ensure that the following are included: Ni, Co, and Mn are preferentially leached out by this leaching agent. The decimal aqueous solution may contain only water, ammonia, and ammonium carbonate, or it may contain other components in addition to these.
[0068] In the second aqueous ammonia solution, the concentration of ammonia is not particularly limited and may be, for example, 1% by mass or more and up to a saturation concentration (i.e., about 35% by mass). The concentration of ammonia in the second aqueous ammonia solution is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. From the viewpoint of leaching ability and ease of handling, an ammonia concentration of 15% by mass to 25% by mass is particularly preferred.
[0069] Ammonium carbonate acts as a pH adjuster. The amount of ammonium carbonate in the second ammonia aqueous solution is preferably such that the pH (at 25°C) of the second ammonia aqueous solution is 9 to 12, more preferably 10 to 11. The concentration of ammonium carbonate in the second ammonia aqueous solution is preferably 0.5 mol / L or more and 3 mol / L or less, more preferably 1 mol / L or more and 3 mol / L or less, and even more preferably 1.5 mol / L or more and 2.5 mol / L or less.
[0070] The amount of secondary ammonia solution used is not particularly limited and may be similar to the amount used in known ammonia leaching methods. For example, the amount of secondary ammonia solution used should be enough to completely immerse the object.
[0071] Here, the ammonia leaching in the second ammonia leaching step S50 may be carried out while supplying gas to the second ammonia aqueous solution. In this case, the selectivity of leaching of Ni, Co, and Mn changes depending on the concentration of oxygen contained in the gas. Specifically, the higher the oxygen concentration of the supplied gas, the more preferentially Ni and Co will leach out. On the other hand, the lower the oxygen concentration of the supplied gas, the more preferentially Mn will leach out.
[0072] The second ammonia leaching step S50 can be carried out, for example, as follows: Prepare a container equipped with heating means such as a heater, temperature measuring means such as a thermometer or temperature sensor, stirring means such as a stirring blade or magnetic stirring bar, etc., as needed. Also, prepare a bubbling device as needed.
[0073] The solid residue and the second ammonia aqueous solution are placed in a container. If necessary, gas is supplied into the reaction vessel containing the second ammonia aqueous solution. Preferably, the gas is supplied to the second ammonia aqueous solution as bubbles by a bubbling device.
[0074] The second ammonia leaching step S50 may be carried out at room temperature (i.e., 25±10℃) or under heating. The leaching temperature is preferably greater than 0℃ and 80℃ or less, more preferably 10℃ or more and 50℃ or less, and even more preferably 15℃ or more and 35℃ or less.
[0075] The leaching time can be appropriately determined according to the leaching temperature. The higher the leaching temperature, the shorter the leaching time can be. The leaching time is, for example, 1 hour or more, preferably 2 hours or more, and more preferably 4 hours or more. On the other hand, from the viewpoint of operational efficiency, the leaching time is, for example, 48 hours or less, preferably 24 hours or less, and more preferably 10 hours or less.
[0076] Stirring is preferable during leaching. The stirring speed is not particularly limited, but is preferably 200 rpm or higher, more preferably 400 rpm or higher, and even more preferably 500 rpm or higher. The stirring speed may be 2000 rpm or lower, 1000 rpm or lower, or 800 rpm or lower.
[0077] Ammonia leaching can be terminated by solid-liquid separation of the filtrate, etc. Ammonia leaching selectively moves Ni, Co, and Mn into the aqueous phase. Therefore, this solid-liquid separation yields a leachate containing Ni ions, Co ions, Mn ions, ammonia, ammonium ions, and carbonate ions (i.e., a second aqueous ammonia solution containing Ni ions, Co ions, Mn ions, ammonia, ammonium ions, and carbonate ions), as shown in Figure 1, and a solid residue containing Al and C. In this manner, the second ammonia leaching step S50 can be carried out. This leachate can be used as a raw material solution containing Ni ions, Co ions, Mn ions, ammonia, ammonium ions, and carbonate ions in the crystallization step S101.
[0078] Here, as described above, when ammonia leaching is carried out while supplying gas into a reaction vessel containing a second aqueous ammonia solution, the selectivity of leaching Ni, Co, and Mn changes depending on the concentration of oxygen in the gas. Therefore, in the second ammonia leaching step S50, by performing two or more leaching stages with different types of supplied gas, it is possible to obtain all of Ni, Co, and Mn with a high recovery rate.
[0079] In one specific embodiment, the second ammonia leaching step S50 includes a Mn leaching step in which Mn is leached into the first aqueous phase by using a second ammonia aqueous solution (A) on the solid residue, and a Ni,Co leaching step in which Ni and Co are leached into the second aqueous phase by using a second ammonia aqueous solution (B) on the solid residue obtained in the Mn leaching step. Here, the amount of dissolved oxygen in the second ammonia aqueous solution (A) during the leaching in the Mn leaching step is less than the amount of dissolved oxygen in the second ammonia aqueous solution (B) during the leaching in the Ni,Co leaching step.
[0080] In this embodiment, in the Mn leaching step, Mn can be recovered in the first aqueous phase with a high recovery rate, and in the Ni,Co leaching step, Ni and Co leaches can be recovered in the second aqueous phase with a high recovery rate. By combining the first aqueous phase and the second aqueous phase, a leachate containing Ni ions, Co ions, Mn ions, ammonia, ammonium ions, and carbonate ions can be obtained, which can be used as the raw material for the crystallization step S101.
[0081] The secondary ammonia aqueous solution (A) used in the Mn leaching process and the secondary ammonia aqueous solution (B) used in the Ni,Co leaching process are both secondary ammonia aqueous solutions as described above, and they may have the same or different compositions. It is advantageous from a control standpoint if the secondary ammonia aqueous solution (A) and the secondary ammonia aqueous solution (B) have the same composition.
[0082] In the Mn leaching process, it is preferable that the leaching is carried out while supplying a gas with an oxygen concentration of 21 vol% or less into the reaction vessel containing the second ammonia aqueous solution (A), such that the amount of dissolved oxygen in the second ammonia aqueous solution (A) during leaching in the Mn leaching process is less than the amount of dissolved oxygen in the second ammonia aqueous solution (B) during leaching in the Ni,Co leaching process. The oxygen concentration of the supplied gas is preferably 18 vol% or less, more preferably 5 vol% or less, and even more preferably 1 vol% or less. The gas supplied in the Mn leaching process is particularly preferably an inert gas (e.g., nitrogen gas, argon gas, etc.). Bubbling is preferred as the method of supplying the gas.
[0083] In the Ni,Co leaching process, it is preferable that the leaching is carried out while supplying a gas with an oxygen concentration of 50% by volume or more into the reaction vessel containing the second ammonia aqueous solution (B), such that the amount of dissolved oxygen in the second ammonia aqueous solution (A) during the Mn leaching process is less than the amount of dissolved oxygen in the second ammonia aqueous solution (B) during the Ni,Co leaching process. The oxygen concentration of the supplied gas is preferably 60% by volume or more, more preferably 90% by volume or more, and particularly preferably 99% by volume or more. The gas supplied in the Ni,Co leaching process is particularly preferably oxygen gas. Bubbling is preferred as the method of supplying the gas. Regarding the amount of gas supplied in the Ni,Co leaching process, it is preferable that the amount of oxygen supplied is equimolar or more relative to the total of Ni and Co, more preferably 2 moles or more and 100 moles or less, and even more preferably 3 moles or more and 100 moles or less.
[0084] In this embodiment, the procedure involves leaching the solid residue using a gas of a predetermined oxygen concentration and a second aqueous ammonia solution (A), followed by solid-liquid separation to obtain the leachate and solid residue. This completes the Mn leaching process. The obtained solid residue is then leached using a gas of a predetermined oxygen concentration and a second aqueous ammonia solution (B), followed by solid separation to obtain the leachate and solid residue. This completes the Ni,Co leaching process. The leachate obtained in the Mn leaching process and the leachate obtained in the Ni,Co leaching process are mixed.
[0085] <Crystallization process S101> In the crystallization step S101, Ni ions (Ni 2+ ), Co ions (Co 2+ ), Mn ions (Mn 2+ ), ammonia (NH3), ammonium ion (NH4) + ), and carbonate ions (CO3 2- A raw material solution containing ) is added to a precipitation solution with a lower ammonia concentration than the raw material solution.
[0086] The raw material solution is typically an aqueous solution. Preferably, the raw material solution includes a solution produced by recycling lithium-ion secondary battery waste. This solution is typically an ammonia leachate containing at least one element selected from the group consisting of Ni, Co, and Mn. In particular, the leachate obtained in the second ammonia leaching step S50 can be used as the raw material solution. However, the raw material solution is not limited to this.
[0087] For example, the raw material solution is an aqueous solution obtained by dissolving a water-soluble salt of Mn in an ammonia leachate containing Ni, Co, ammonia, and ammonium carbonate, which is obtained by the above-mentioned recycling method for lithium-ion secondary battery waste. For example, the raw material solution is an aqueous solution obtained by adjusting the molar ratio of Ni, Co, and Mn by adding at least one of a water-soluble salt of Ni, a water-soluble salt of Co, and a water-soluble salt of Mn to the leachate obtained in the second ammonia leaching step S50. Alternatively, for example, the raw material solution is an aqueous solution obtained by dissolving a water-soluble salt of Ni, a water-soluble salt of Co, a water-soluble salt of Mn, ammonia, and ammonium carbonate in water.
[0088] The pH of the raw material solution at 25°C is preferably in the range of 10.0 to 12.0 from the viewpoint of preventing the precipitation of Ni, Co, and Mn during storage. The pH of the raw material solution at 25°C is important for the Ni ions, Co ions, Mn ions, ammonia (NH3), and ammonium ions (NH4) contained in the raw material solution. + ), and carbonate ions (CO3 2- It can be adjusted by the amount or concentration of ).
[0089] Therefore, Ni ions, Co ions, Mn ions, ammonia (NH3), and ammonium ions (NH4) are present in the raw material solution. + The amount or concentration of the raw material is preferably such that the pH of the raw material solution falls within the above range.
[0090] The molar ratio of Ni, Co, and Mn in the raw material solution may be the same as the desired molar ratio of the positive electrode active material to be manufactured. The amount of carbonate ions in the raw material solution is not particularly limited, but it is preferably 1 molar time or more relative to the total amount of Ni, Co, and Mn, and more preferably 1.5 molar times or more. Even if the amount of carbonate ions in the raw material solution is less than 1 molar time relative to the total amount of Ni, Co, and Mn, the crystallization step S101 can be carried out by including carbonate ions in the precipitation solution.
[0091] The precipitation solution functions to precipitate Ni ions, Co ions, Mn ions, and carbonate ions contained in the raw material solution as a composite carbonate containing Ni, Co, and Mn (i.e., nickel-cobalt-manganese composite carbonate) when the raw material solution is added. Therefore, the ammonia concentration in the precipitation solution is lower than the ammonia concentration in the raw material solution.
[0092] The precipitation solution is not particularly limited as long as its ammonia concentration is lower than that of the raw material solution. The precipitation solution may be an ammonium ion donor. For example, the precipitation solution may be an aqueous solution of an ammonium salt such as ammonium carbonate, ammonium sulfate, or ammonium chloride. Among these, ammonium carbonate is preferred because it is composed only of components contained in the raw material solution (i.e., it does not contain impurities) and can supply carbonate ions to promote the precipitation of carbonates. Water (e.g., deionized water, distilled water, etc.) can also be used as the precipitation solution. When water is used, the preparation of the precipitation solution is easy and it is also advantageous in terms of cost.
[0093] In the starting liquid, Ni ions, Co ions, and Mn ions form ammine complexes with ammonia and ammonium ions, respectively, resulting in a stable state for Ni, Co, and Mn. Here, crystallization reactions of Ni, Co, and Mn can be induced by evaporating ammonia from the starting liquid. However, among the complexes of Ni, Co, and Mn, the Mn complex is the most unstable. Therefore, in the initial stages of the crystallization reaction, a large amount of Mn precipitates, while in the later stages, only a small amount of Mn precipitates. As a result, the proportion of Mn is high in the center of the precipitated carbonate particles, and low in the surface layers of the particles. Thus, Mn is unevenly distributed in the center of the carbonate particles. This is because the change in ammonia concentration is gradual when evaporating ammonia from the starting liquid.
[0094] In the manufacturing method disclosed herein, the ammonia concentration in the precipitation solution is lower than the ammonia concentration in the raw material solution. Therefore, when the raw material solution is added to the precipitation solution, the ammonia concentration near the ammine complex decreases rapidly, and all of the Ni, Co, and Mn complexes in the raw material solution become unstable. As a result, Ni, Co, and Mn all precipitate at roughly the same rate. Consequently, the uneven distribution of Mn in the center of the precipitated carbonate particles is suppressed.
[0095] From the viewpoint of effectively exhibiting these effects, the pH of the precipitation solution at 25°C is preferably less than 10.0, more preferably 9.5 or less, even more preferably 9.0 or less, and particularly preferably 8.0 or less, as a guideline for ammonia concentration. The lower limit of the pH of the precipitation solution at 25°C is not particularly limited. When water is used as the precipitation solution, the pH may drop to about 5.2 due to the dissolution of carbon dioxide in the atmosphere into the water. Taking this into consideration, the lower limit of the pH of the precipitation solution at 25°C may be 5.2 or higher, preferably 6.5 or higher, and more preferably 7.0 or higher.
[0096] Crystallization can be carried out in the following way, for example: Prepare a known reaction vessel used for crystallization. The reaction vessel may be equipped with heating means such as a heater, temperature measuring means such as a thermometer or temperature sensor, pH measuring means such as a pH meter, stirring means such as a stirring blade or magnetic stirring bar, etc.
[0097] The precipitation solution is added to this reaction vessel. Then, the raw material solution is added to the precipitation solution. Here, from the viewpoint of making a large change in ammonia concentration, it is preferable to add the raw material solution dropwise to the precipitation solution. As the raw material solution is added dropwise to the precipitation solution, a reaction solution is formed in the reaction vessel.
[0098] The pH of the reaction solution at 25°C during crystallization is preferably 10.0 or less, and more preferably 9.5 or less. Therefore, it is preferable to adjust the amount of raw material solution and the rate of addition so that the pH of the reaction solution does not exceed the above range.
[0099] The crystallization temperature is not particularly limited as long as the crystallization reaction occurs. Crystallization may be carried out at room temperature (i.e., 25°C ± 10°C) or under heating. The crystallization temperature is preferably 45°C or higher, more preferably 60°C or higher, and even more preferably 80°C or higher. On the other hand, the crystallization temperature may be below the boiling point of the reaction solution and may be below 100°C.
[0100] Stirring is preferable during crystallization. The stirring speed is not particularly limited, but is preferably 200 rpm or higher, more preferably 400 rpm or higher, and even more preferably 600 rpm or higher. The stirring speed may be 2000 rpm or lower, 1000 rpm or lower, or 800 rpm or lower.
[0101] The crystallization time is not particularly limited and can be appropriately determined according to the leaching temperature, stirring speed, etc. The crystallization time is, for example, 10 minutes or more, preferably 1 hour or more, and more preferably 2 hours or more. From the viewpoint of operational efficiency, the crystallization time is, for example, 48 hours or less, preferably 24 hours or less, more preferably 12 hours or less, and even more preferably 6 hours or less.
[0102] Crystallization can precipitate carbonates containing Ni, Co, and Mn. The precipitated carbonates containing Ni, Co, and Mn can be recovered according to known methods. For example, the precipitated carbonates containing Ni, Co, and Mn can be separated from the aqueous phase by solid-liquid separation such as filtration, washed with water, and then dried to recover the carbonates containing Ni, Co, and Mn.
[0103] The aqueous phase after solid-liquid separation contains ammonia and unreacted ammonium carbonate. This aqueous phase can be reused in the process of recycling lithium-ion secondary battery waste by adjusting the amount of components, pH, etc., and using ammonia and ammonium carbonate. Alternatively, ammonia and ammonium carbonate can be recovered from this aqueous phase and reused in the processes of recycling lithium-ion secondary battery waste by using ammonia and ammonium carbonate.
[0104] As described above, the crystallization step S101 yields a carbonate containing Ni, Co, and Mn, which is a precursor of the positive electrode active material (i.e., nickel-cobalt-manganese composite carbonate). This carbonate can be used in the production of the positive electrode active material for lithium-ion secondary batteries. This will be explained in detail below.
[0105] <Method for manufacturing positive electrode active material> A method for producing a positive electrode active material includes the steps of obtaining a precursor by the method for producing a positive electrode active material precursor described in this disclosure (hereinafter also referred to as the "precursor preparation step"), mixing the precursor with a lithium compound to obtain a mixture (hereinafter also referred to as the "mixing step"), and calcining the mixture (hereinafter also referred to as the "calcination step").
[0106] The manufacturing method for this positive electrode active material will now be described in detail. The precursor preparation step is as described above in the description of the manufacturing method for the precursor of the positive electrode active material in this disclosure.
[0107] The precursor may be heat-treated before the mixing step. At this time, the precursor may be converted into an oxide. A composite oxide containing Ni, Co, and Mn also serves as a precursor for the positive electrode active material. When converted to an oxide, the heat treatment temperature is preferably 300°C to 1000°C. The heat treatment time is preferably 1 hour or more, more preferably 1 hour to 48 hours, and even more preferably 5 hours to 24 hours. The heat treatment can be carried out in air.
[0108] The lithium compound used in the mixing process serves as the Li source for the positive electrode active material. Examples of lithium compounds that can be converted to oxides by calcination include lithium carbonate, lithium nitrate, and lithium hydroxide.
[0109] The mixing ratio of the lithium compound to the precursor may be appropriately determined according to the desired composition of the positive electrode active material. For example, in the positive electrode active material, the ratio of Li to other metals (usually the sum of Ni, Co, and Mn) is preferably 0.95 to 1.15. Therefore, preferably, the lithium compound and the precursor are mixed such that the molar ratio of Li contained in the lithium compound to the metals contained in the precursor (usually the sum of Ni, Co, and Mn) is 0.95 to 1.15.
[0110] If it is desired to introduce a metal other than Li (also called another metal) that is not present in the precursor into the positive electrode active material, other metal sources may be further mixed in according to known methods.
[0111] The mixing of lithium compounds and precursors can be carried out according to known methods. For example, the precursor and lithium compound can be mixed using a mixing device such as a shaker mixer, V blender, ribbon mixer, Julia mixer, or Redige mixer. This will yield a mixture.
[0112] The firing process can be carried out according to known methods. For example, the firing of the mixture can be carried out using a known electric furnace or the like. As for the firing atmosphere, an oxidizing atmosphere is preferred from the viewpoint of suppressing oxygen vacancies in the positive electrode active material. A suitable oxidizing atmosphere is one with an oxygen concentration of 10% by volume or more, which may be an air atmosphere or an oxygen atmosphere (i.e., an atmosphere with a higher oxygen concentration than air). The firing temperature is 650°C to 1000°C, preferably 700°C to 900°C. The firing time is 3 hours to 8 hours, preferably 3.5 hours to 7.5 hours.
[0113] As described above, lithium nickel manganese cobalt composite oxide, which is the positive electrode active material, can be manufactured. The positive electrode active material can be used in lithium-ion secondary batteries according to known methods.
[0114] The following describes examples relating to this disclosure in detail, but this disclosure is not intended to be limited to those shown in such examples.
[0115] [Preparation of raw material liquid] Ni metal, Co metal, and Mn oxide were dissolved in an aqueous solution of ammonium carbonate. The molar ratio of Ni, Co, and Mn was 90:5:5. The amount of ammonium carbonate was 1.5 times the total amount of Ni and Co. The ammonium concentration of the aqueous solution was 13 mol / L. The resulting solution was used as the raw material. The pH of the raw material solution at 25°C, measured by the following method, was 11.
[0116] [pH measurement] In the examples and comparative examples, the pH of each solution was measured using a commercially available pH meter (Horiba F-71S desktop pH meter).
[0117] [Comparative Example 1] The above raw material liquid was added to the reaction vessel. It was heated to 80°C, and the ammonia was evaporated while stirring to allow the crystallization reaction to proceed. Small samples of the crystallized product and reaction solution were taken at regular intervals, and after cooling, the pH of the reaction solution at 25°C was measured. Heating was stopped when the pH fluctuation in the reaction vessel became small. The post-crystallization pH at this point was 9.3. Subsequently, solid-liquid separation was performed by filtration, and the crystallized product was obtained by washing with water.
[0118] [Example 1] An aqueous solution of ammonium carbonate with a pH of 9.0 at 25°C was prepared as the precipitation solution. This was added to the reaction vessel. The precipitation solution was heated to 80°C, and while stirring, the crystallization reaction was carried out by supplying the above-mentioned raw material solution to the precipitation solution dropwise. Small samples of the crystallized product and reaction solution were taken at regular intervals, and after cooling, the pH of the reaction solution at 25°C was measured. When the pH of the reaction solution in the reaction vessel rose to 10.7, the dropwise addition of the raw material solution and heating were stopped. At this point, the pH after crystallization was 10.7. Subsequently, solid-liquid separation was performed by filtration, and the crystallized product was obtained by washing with water.
[0119] [Example 2] The dropping rate of the raw material solution was adjusted to control the pH of the reaction solution in the reaction vessel so that it would not rise during the reaction. The crystallized product was obtained in the same manner as in Example 1, except that the dropping of the raw material solution and heating were stopped when the pH of the reaction solution in the reaction vessel rose to 9.4.
[0120] [Example 3] Pure water with a pH of 7.0 at 25°C was prepared as the precipitation solution. This was added to the reaction vessel. The precipitation solution was heated to 80°C, and while stirring, the above-mentioned raw material solution was added to the precipitation solution dropwise. When the pH of the reaction solution in the reaction vessel rose to 10.5, the dropwise addition of the raw material solution and heating were stopped. After that, solid-liquid separation was performed by filtration, and the precipitate was obtained by washing with water.
[0121] [Example 4] The dropping rate of the raw material solution was adjusted to control the pH of the reaction solution in the reaction vessel so that it would not rise during the reaction. The crystallized product was obtained in the same manner as in Example 3, except that the dropping of the raw material solution and heating were stopped when the pH of the reaction solution in the reaction vessel rose to 9.2.
[0122] [Example 5] The crystallized product was obtained in the same manner as in Example 4, except that the temperature inside the reaction vessel was set to 90°C.
[0123] [Example 6] The crystallized product was obtained in the same manner as in Example 4, except that the temperature inside the reaction vessel was set to 70°C.
[0124] [Example 7] The crystallized product was obtained in the same manner as in Example 4, except that the temperature inside the reaction vessel was set to 60°C.
[0125] [Example 8] The crystallized product was obtained in the same manner as in Example 4, except that the temperature inside the reaction vessel was set to 45°C and the addition of the raw material solution and heating were stopped when the pH of the reaction solution inside the reaction vessel rose to 9.4.
[0126] [Evaluation of Mn segregation rate] Samples were prepared by exposing the particle cross-sections of the crystallized material obtained in Comparative Example 1 and each example, according to a standard method. The samples were observed using a scanning electron microscope (SEM), and particles with a particle size of several μm were selected. The central and surface regions of the selected particles were analyzed by energy-dispersive X-ray spectroscopy (EDS), and the abundance ratio of Mn in the central and surface regions was determined. For 10 particles, the value of "Mn abundance ratio in the central region / Mn abundance ratio in the surface region" was calculated, and the average value was defined as the Mn segregation ratio. The results are shown in Table 1. Note that the Mn segregation ratio when Mn is not segregated is 1.0. For reference, the particle cross-sectional image, Mn mapping image of the particle cross-section, and Ni mapping image of the particle cross-section of Comparative Example 1 are shown in Figures 4 to 6, respectively. The particle cross-sectional image, Mn mapping image of the particle cross-section, and Ni mapping image of the particle cross-section of Example 4 are shown in Figures 7 to 9, respectively.
[0127] [Table 1]
[0128] As shown in Figures 4-6 and Table 1, in Comparative Example 1, where carbonate was precipitated by evaporating ammonia, Mn was concentrated in the center of the particles, and its proportion (ratio of Mn in the center / ratio of Mn in the surface layer) was extremely high at 90.9.
[0129] On the other hand, as shown in Figures 7-9 and Table 1, in Examples 1-8, where carbonates were precipitated by dropping the raw material solution into a precipitation solution with a lower ammonia concentration than the raw material solution, the segregation of Mn in the center of the particles was suppressed. Furthermore, a comparison of Example 1 and Example 2 shows that dropping the raw material solution in a way that prevents the pH from rising during crystallization allows the crystallization reaction to proceed at a sufficiently fast ammonia evaporation rate, thus further suppressing the segregation of Mn. In addition, a comparison of Example 2 and Example 4 shows that a lower pH of the precipitation solution further suppresses the segregation of Mn. This is thought to be because the absence of an ammonia source in the precipitation solution in the reaction vessel causes a rapid decrease in the ammonia concentration of the Ni, Co, and Mn ammine complexes in the raw material solution, making all the ammine complexes unstable, resulting in all of Ni, Co, and Mn precipitating at roughly the same rate.
[0130] From the above results, it can be seen that the method for producing the cathode active material precursor of this disclosure can suppress the uneven distribution of Mn in the center of the particle.
[0131] The specific examples of this disclosure have been described in detail above, but these are merely illustrative and do not limit the scope of the claims. The technologies described in the claims include various modifications and changes to the specific examples described above.
[0132] In other words, the method for producing the precursor of the positive electrode active material and the method for producing the positive electrode active material of this disclosure are as follows: [1] to [9]. [1] The process includes adding a raw material solution containing Ni, Co, Mn, ammonia, ammonium ions, and carbonate ions to a precipitation solution to precipitate a carbonate containing Ni, Co, and Mn. A method for producing a precursor of a positive electrode active material, wherein the concentration of ammonia in the deposition solution is lower than the concentration of ammonia in the raw material solution. [2] The manufacturing method according to item [1], wherein the pH of the raw material solution at 25°C is 10.0 to 12.0, and the pH of the precipitation solution at 25°C is less than 10.0. [3] The manufacturing method according to item [2], wherein the pH of the precipitation solution at 25°C is 9.5 or less. [4] The manufacturing method according to item [2], wherein the pH of the precipitation solution at 25°C is 8.0 or less. [5] The manufacturing method according to any one of items [1] to [4], wherein the precipitation solution is water or an aqueous solution of ammonium carbonate. [6] The manufacturing method according to any one of items [1] to [4], wherein the precipitation solution is water. [7] The manufacturing method according to any one of items [1] to [6], wherein the pH of the reaction solution obtained by adding the raw material solution to the precipitation solution is 10.0 or less at 25°C. [8] The manufacturing method according to any one of items [1] to [7], wherein the raw material liquid includes a liquid produced by recycling lithium-ion secondary battery waste. [9] A step of obtaining a precursor by a method for producing a positive electrode active material precursor described in any one of the items [1] to [8], A step of mixing the obtained precursor with a lithium compound to obtain a mixture, and A step of firing the obtained mixture. A method for producing a positive electrode active material containing the active material.
Claims
1. The process includes adding a raw material solution containing Ni, Co, Mn, ammonia, ammonium ions, and carbonate ions to a precipitation solution to precipitate a carbonate containing Ni, Co, and Mn. A method for producing a precursor of a positive electrode active material, wherein the concentration of ammonia in the deposition solution is lower than the concentration of ammonia in the raw material solution.
2. The manufacturing method according to claim 1, wherein the pH of the raw material solution at 25°C is 10.0 to 12.0, and the pH of the precipitation solution at 25°C is less than 10.
0.
3. The manufacturing method according to claim 2, wherein the pH of the precipitation solution at 25°C is 9.5 or less.
4. The manufacturing method according to claim 2, wherein the pH of the precipitation solution at 25°C is 8.0 or less.
5. The manufacturing method according to claim 1, wherein the precipitation solution is water or an aqueous solution of ammonium carbonate.
6. The manufacturing method according to claim 1, wherein the precipitation liquid is water.
7. The manufacturing method according to claim 1, wherein the pH of the reaction solution obtained by adding the raw material solution to the precipitation solution is 10.0 or less at 25°C.
8. The manufacturing method according to claim 1, wherein the raw material liquid includes a liquid produced by recycling lithium-ion secondary battery waste.
9. A step of obtaining a precursor by the method for producing a positive electrode active material precursor described in claim 1, A step of mixing the obtained precursor with a lithium compound to obtain a mixture, and A step of firing the obtained mixture. A method for producing a positive electrode active material containing the active material.
Citation Information
Patent Citations
Positive electrode active material precursor for non aqueous electrolyte secondary cell, positive electrode active material for non aqueous electrolyte secondary cell, method for manufacturing positive electrode active material precursor for non aqueous electrolyte secondary cell, and method for manufacturing positive electrode active material for non aqueous electrolyte secondary cell
WO2017119457A1